Family caregiving as a pathway to strengthen health outcomes in India - Yan, Shirley Du; Jagtiani, Tanaya; Sharma, Poornima; Rangarajan, Arjun; Issar, Bhavana; Kanjilal, Madhura; Deo, Prachi; Rana, Smriti; Murthy, Seema; Alam, Shahed; Mor, Nachiket (Frontiers in Public Health, 2025)
Although India’s health outcomes have improved, progress can still be made to reduce the health burden from tuberculosis, noncommunicable diseases, and maternal and neonatal health. In order to address challenges such as healthcare workforce shortages or sub-optimal time with healthcare workers, health systems can involve family caregivers who are already playing an active, informal role to support patients. Their formal involvement to support patients has been associated with improved health outcomes in health conditions. Formal support for family caregivers aligns with other priority health strategies, such as self-care, universal healthcare, and shifting demographic trends in India. Inspiration can be drawn from existing interventions that support family caregivers: training and education delivered through the public health system, caregiver support groups, community volunteers to support palliative patients, and interventions for specific patient populations (i.e., palliative care or for children with disabilities). For India, though there are no comprehensive policies that finance informal caregiver inclusion, there are examples to draw from globally. Finally, we recommend tenets of how to best engage with family caregivers, which can lead to meaningful caregiver involvement for improved health outcomes: leveraging trusted sources, focusing on actionable skills, providing just-in-time engagement, designing for diverse contexts, and ensuring caregiver safety.